2019
DOI: 10.1002/bdr2.1494
|View full text |Cite
|
Sign up to set email alerts
|

Selected acculturation factors and birth defects in the National Birth Defects Prevention Study, 1997–2011

Abstract: Background Acculturation has been examined with respect to various pregnancy adverse outcomes, including birth defects. Given the mixed and limited findings on the association between nativity and birth defects, we sought to further explore parental nativity and years lived in the U.S. across a range of defects. Methods Data from the National Birth Defects Prevention Study were used for this analysis. Infants with one of 46 major isolated birth defects (30 noncardiac/16 cardiac conditions) and infants without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…We found an approximately 30% diminished risk of septal defects among NH Black foreign‐born mothers compared to U.S.‐born. These findings follow previously observed diminished aORs in a recently conducted NBDPS acculturation analysis which found that both mothers and fathers who were foreign‐born (≤5 years in the United States) were also 30% less likely to have infants diagnosed with septal defects (Hoyt et al, ). As with limb deficiencies, a constellation of factors may be present to modify risk for not just septal defects, but a range of CHDs—many of which were found in this analysis to be nonsignificantly diminished in infants born to foreign‐born mothers compared to U.S.‐born (see Table ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We found an approximately 30% diminished risk of septal defects among NH Black foreign‐born mothers compared to U.S.‐born. These findings follow previously observed diminished aORs in a recently conducted NBDPS acculturation analysis which found that both mothers and fathers who were foreign‐born (≤5 years in the United States) were also 30% less likely to have infants diagnosed with septal defects (Hoyt et al, ). As with limb deficiencies, a constellation of factors may be present to modify risk for not just septal defects, but a range of CHDs—many of which were found in this analysis to be nonsignificantly diminished in infants born to foreign‐born mothers compared to U.S.‐born (see Table ).…”
Section: Discussionsupporting
confidence: 88%
“…A constellation of exposures present among U.S.‐born mothers (e.g., higher levels of alcohol, smoking, and prescription/recreational drug use), may place them at higher risk for limb defects than their foreign‐born counterparts. As observed in a previous NBDPS analysis (Hoyt et al, ), foreign‐born mothers were less likely to report: being overweight/obese; having consumed alcohol or high levels of caffeine (300 + mg/day); having smoked or taken illicit drugs (cocaine/methamphetamine) during the periconceptional period; or having been previously diagnosed with high blood pressure. In our examination, foreign‐born NH Black mothers were also more educated (12+ years) compared to U.S.‐born mothers (which was not observed in the other acculturation analysis indicated above).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations